An Extension of Polak-RibiÃ¨re-Polyak Method - Dawahdeh, Mahmoud; Mamat, Mustafa; Alhawarat, Ahmad; Rivaie, Mohd; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
The conjugate gradient method has been widely used for finding solution for the large-scale unconstrained optimization. Fields such as computer science and engineering are the two most frequently engaged, because of its simplicity, the speed of getting the solution and the minimal storage requirement. This study presents an extended conjugate gradient method of Polak-RibiÃ¨re-Polyak with the strong Wolfe-Powell (SWP) line search satisfying some properties such as sufficient descent and global convergence. For the purpose of experimentation, a set of 141 test problems have been used. The results showed that our proposed method has surpass the others in terms of efficiency and robustness.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â